Role of bread yeast to reduce the harmful effects of salt stress on seed germination and growth of wheat seedling - Abraheem, B. A.; Mohammad, O. H.; Jasem, N. .A; Joad, M. S.; Enad, N. K. (Journal of Kerbala for Agricultural Sciences, 2016)
A factorial experiment was carried out at the laboratory of the Department of Field Crop in the College of Agriculture-University of Baghdad, during spring season 2014. Randomized complete block design was used with four replications, to enhance Wheat Triticum aestivum L. seeds to Salt tolerance at concentrations (0.0, 2.0, 4.0, 8.0 and 12.0 %) by soaking seeds with Yeast Extract Saccharomyces cerevisiae at concentrations(0, 2, 4, 8 and 12g.l-1) . Sodium Hypochlorite (1%) was used to Sterilize seeds for three minute, and washing with sterile water, soaking with Yeast Extract for 24 hour. Ten seeds of wheat sown in Petri dish 9cm diameter, on filter paper and Watered With different salinity levels with 5ml daily until the end of the experiment. Results showed that the salinity levels 0.5, 1.0 and 1.5% significantly decreasing first germination count percentage, final germination count percentage, coleoptile and root length, fresh and dry weights. However salinity level 2% prevented germination. Yeast significantly increased plant efficiency to salt tolerance in the first germination count, coleoptile and root lengths, fresh and dry weights. The high level 8 g.l-1 of yeast significantly increased all studied characters except coleoptile length which had been increased by the highest level (12g.l-1). The most interactions appeared to be significant. We can conclude that the yeast shown an ability to increase the indicator of germination values of wheat seedlings under the salinity 1.5% of NaCl or in the absence of the salinity.